Web-Based Acceptance Of Candidate Mustahiq Information System (Cangkir Yadufa Social Religious Foundation): Sistem Informasi Penerimaan Calon Mustahiq Berbasis Web ( Yayasan Keagamaan Sosial Cangkir Yadufa) - Andre Pramanta Widianto; Cindy Taurusta (Academia Open, 2021)
In a foundation there is a need for fast and fast mustahiq data storage. This socio-religious foundation for the yadufa cup is still stored manually. The previous data storage was still using Microsoft Excel. In the current era technology is needed, information systems to make it easier for admins to complete their work. From manual work to computerized. The writing uses data collection methods in the form of interviews with the admin of the foundation to find out the problems. Then do a literature study by reading the appropriate previous research. Then analyze the main problems that exist to determine the boundaries of the problem. The conclusion of this study aims to research the manufacture of "WEB- based information system for acceptance of mustahiq candidates (Yayasan socio- religious cup Yadufa) is to create and provide an information system that can be used to store data accurately, record recipients of mustahiq participants quickly and accurately.